SCIENCE-BASED ACUPRESSURE SELF-CARE EDUCATION FOR PREGNANT WOMEN AT CESAREAN RISK - Sutrisna altahira; Suryo Ediyono (Jurnal Multidisipliner Bharasumba, 2026)
The rate of cesarean section has increased significantly and has become a major concern in maternal healthcare services. Therefore, promotive and preventive strategies are needed to enhance the independence of pregnant women, one of which is through the application of self-care acupressure as a safe and practical non-pharmacological complementary therapy. This study aimed to evaluate the effectiveness of self-care acupressure in improving knowledge, practical skills, and independence among pregnant women at risk of cesarean section in the working area of Katobengke Public Health Center, Baubau City. A quantitative approach with a quasi-experimental one group pretest–posttest design was used. The study was conducted in 2026 involving 30 participants selected through purposive sampling. Before the intervention, most respondents had low knowledge levels. After the education program, knowledge improved significantly, with statistical analysis showing a meaningful difference before and after the intervention.